The Influence of Perceptions of Price, Product Completeness, and Service Quality on Purchasing Decisions Mranggen Media Graphics Shop - Setiawan, Budi; Latifah, Nur Aini; Sulistyorini, Sulistyorini; Simamora, Elisabeth Rotua (Economics and Business Solutions Journal, 2024)
Science and technology are developing very fast from time to time. It requires companies to work quickly, innovatively, and creatively to remain competitive with their competitors and increase purchasing decisions at the Graphic Media Manager store. This research analyzes the influence of Price Perceptions, Product Completeness, and Excellent Service Quality on purchasing decisions at the Graphic Media Mranggen store. This research uses a purposive sampling method. The sample used in this research was 96 respondents from the customers of the Graphic Media Mranggen store. Data analysis in this research used the SPSS version 25 program. Tests included validity tests by comparing calculated r with r tables, reliability tests using Cronbach Alpha, and classical assumption tests, which included normality tests, multicollinearity tests, and heteroscedasticity tests. Multiple analysis tests are used to test how much influence the independent variable has on the dependent variable, prove the research hypothesis, and test the hypothesis with the t-test-test, f-test, and coefficient of determination test (R 2 ). This research shows that the variables of Price of Perception, Product Completeness, and Excellent Service Quality positively and significantly affect purchasing decisions at the Graphic Media Mranggen store. The results of this research give the impression that price perception, product completeness, and excellent service quality are factors that need to be considered to improve consumer purchasing decisions to achieve the goals set by the company.